Prospects and pitfalls of a university-community partnership using Jatropha for sustainable rural development in a Nigerian community. Issue 1 (1st January 2018) - Baker, Lynne R.
Abstract: Jatropha ( Jatropha curcas ) has been widely touted as a feedstock for biofuel production and way to combat rural poverty. In some cases, using Jatropha for rural economic development has led to unfulfilled expectations and failed programs. I investigated the expectations of an agricultural community in Nigeria toward a Jatropha biodiesel development project initiated by a private university and how community and project leaders perceived the impact of the program's eventual abandonment. Willingness to adopt the project appeared largely due to its association with the university and expatriate staff. Community leaders' enthusiastic support resulted in high expectations of poverty alleviation and community improvements. Given the community-perceived slow progress of the project and its ultimate dissolution, the community–university relationship and intra-community relations, including potential disempowerment of community leaders, were affected. The overall impact was, however, mitigated by other university-backed community programs and continued support by community leaders for using Jatropha for development.